Eco-efficient analysis of thermal regulations applied to thermal envelopes of a dwelling in Chile - Rocha Rubilar, Aracely; Claudia Muñoz Sanguinetti; Gerardo Salezer; Balic, Gabriel Cereceda (Revista de la Construcción. Journal of Construction, 2023)
The aim of this study is to comparatively evaluate the eco-efficient performance of the only two mandatory thermal regulations applied in Chile: The General Urban Planning and Construction Ordinance (OGUC), and the Atmospheric Decontamination Plans (PDA). Considering the PDA of the communes of Temuco and Padre las Casas, and the system limits of UNE-EN 15978:2012 for the "product" and "use" stages, this study covered the indicators of energy, carbon footprint, economic cost and emissions of fine particulate matter (PM2.5), on thermal envelopes of a house. Applying the PDA over the OGUC, the results indicate that: First, the contained energy increases by 12.4%, the carbon footprint by 8.1% and the economic cost by 7.8% in the stage of product; and second, it reduces the demand for heating, fuel consumption, carbon footprint, and PM2.5 emissions, by 19.4%, in the use stage. Finally, the study concludes that, for Chilean homes to improve their eco-efficient performance, an evaluation with a life cycle cost analysis (LCCA) approach, which allows analyzing their evolution over time, must be included in the mandatory thermal regulations that regulate them.